URGENSI PENDIDIKAN SEKS PADA ANAK USIA DINI - Alucyana Alucyana; Raihana Raihana; Dian Tri Utami (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
Abstract We always assume that the world of children is a beautiful world, happy, safe and far from problems. Their time is always filled with fun and play. This statement is not entirely true, because behind a world filled with joy in children, real discomfort always lurks them. Negligence of parents who unwittingly make them trapped in unsafe conditions, for example, becoming victims of sexual abuse in early childhood. Not infrequently the perpetrators of sexual harassment are known people and people closest to them. Early childhood often becomes a victim because of verbal limitations and still lack of ability to express what is felt and experienced in detail and in detail. This condition is further strengthened by the lack of understanding of early childhood on the part of their body that can be touched and do not include what they should do when the unpleasant condition occurs. Therefore providing sex education to early childhood is important, so that the incidence of abuse in early childhood that can result in long-term trauma can be avoided. Sex education in early childhood is presented, of course, by following the age of their development and means of learning media that is suitable for early childhood. This sex education can be done by storytelling method, or playing pretend (pretend play)